Placental mesenchymal dysplasia: case report with gross and histological findings - Marcello Pecoraro Toscano (Autopsy and Case Reports, 2014)
Placental mesenchymal dysplasia (PMD) is a rare placental disorder characterized by placental enlargement and areas of abnormal, enlarged, grape-like villi. This condition may resemble a partial hydatidiform mole and may occur associated with Beckwith–Wiedemann syndrome (BWS) or in phenotypically normal fetuses. There were 110 cases reported so far. We describe one case with typical gross and microscopic placental lesions.